Screening of Domestic Violence During Pregnancy - Sobia Nawaz Malik, Maliha Sadaf , Farzana Kazmi, Sadaf Tufail , (Journal of Rawalpindi Medical College, 2012)
Background: To determine the magnitude and prevalence of domestic violence during pregnancy. Methods In this descriptive study five hundred and sixty women who presented for routine antenatal check up were interviewed. Physical abuse during pregnancy was the primary outcome measure as determined by the USAID's domestic violence module 2011. Frequencies of different forms of abuse were measured. Results Physical abuse was recorded in 12.6%. Majority (88.5%) experienced multiple forms of abuse.Slapping (80%) was the commonest. Conclusion: Domestic violence during pregnancy, due to its harmful feto-maternal implications, is an issue which needs to be addressed